An intimal sarcoma of pulmonary artery mimicking pulmonary embolism: a case report and literature review - Liu, Xiaojing (Respirol Case Rep, 2017)
Pulmonary artery intimal sarcoma is a highly aggressive disease, and is most often misdiagnosed as pulmonary thromboembolism (PTE) due to the similar clinical symptoms and its rarity, which leads to the use of inappropriate treatments such as prolonged anticoagulant therapy. We reported a case of pulmonary artery intimal sarcoma in a patient who was misdiagnosed as having PTE. Pathology after surgery confirmed malignant disease. We concluded that when a patient presents with mild clinical manifestations yet with strong imaging manifestations, pulmonary artery malignancy should be suspected.